The effects and differences of sprint interval training, endurance training and the training types combined on physiological parameters and exercise performance - Hurst, R. A.; Kass, L. S. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Sprint Interval Training (SIT) is a time efficient way in order to elicit similar changes as Endurance Training (ET) on aerobic capacity. Minimal research is currently available combining these training types, in a single training session to obtain potentially greater benefits over the same period of time. The aim of this study was to compare and contrast the effects of SIT, ET and combined training on physiological parameters and exercise performance after an 8 week training programme. Twenty nine participants volunteered to take part in the 8 week matched paired training study (age;35.1±13.1 years, female;16). All participants undertook a preliminary VO2max test and baseline measurements recorded. Participants were matched paired into groups based on sex, VO2peak (ml/kg/min) and resting heart rate (HR), then randomly assigned into a SIT, ET, COMB or control group. Training was undertaken three times per week. SIT group undertook; 5-8 5-second sprints with intervals of 30 seconds, twice, interspaced with 4 minutes rest on a cycle ergometer. ET group cycled for 40-60 minutes over 8 weeks, at 60% of VO2peak. COMB group undertook combination of the above two protocols based on a pilot study undertaken. The CON group did not undertake any training regime. After 4 and 8 weeks of the training, all participants undertook a VO2max test and baseline measures were re-recorded. Prior to each VO2max test, capillary blood samples were taken for the colorimetric assessment of cholesterol. One way ANOVA, K independent samples and Repeated measures ANOVA with Bonferroni correction were used for statistical analysis. The 4 groups were not significantly different at baseline in VO2max (p=0.993) and resting HR (p=0.790) after being match paired into groups. There were no significant differences in VO2max between the training groups after 4 or 8 weeks (p>0.05), significant changes were seen within SIT (p=0.06), ET (p=0.029) and COMB (p=0.004). Significant differences were evident in the resting HR between the CON and SIT (p=0.005) and between COMB and CON (p=0.037). Significance was indicated within the training groups in resting HR; SIT (p=0.006), COMB (p=0.016), ET (p=0.036). Significance was shown in triglycerides after 8 weeks, between CON and SIT (p=0.048). In terms of age, significant difference was seen in VO2max between those aged <35 years and >35 years, after 4 (p=0.022) and 8 weeks (p=0.020) of training. No significant differences were measured in AT, resting SV, resting Q, resting BP & body fat percentage between the training groups (p>0.05), changes within training types were evident (p<0.05). Overall the results indicate when ET is substituted partly with SIT, greater beneficial effects are obtained in numerous variables. Furthermore, a lower duration of sprint i.e. 5 seconds, as in this study provided comparable benefits to previous studies that used longer sprint durations. These findings demonstrate that a short time frame or a combined approach to training, can assist with improving health, performance and cardiorespiratory fitness parameters.